Design Implementation and Operation of an Education Laboratory-Scale Microgrid - (:unkn) unknown (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2021)
To enable more wide-scale exploitation of renewable energy sources (RESs), distributed generations (DGs) as in microgrids have gained prominence recently. This study describes the design, modeling, implementation, and operation of a microgrid, in which a standalone hybrid power system has been installed for an education and research laboratory. The unstable nature of RESs results in power compatibility issues on DGs. Therefore, providing a decent power flow from renewables to loads is the scope of this paper. To satisfy defined load profiles and sustain the power with the desired level, the design and operation of power converters are a remarkable part of performing microgrids as well. For a robust microgrid structure, the presented control algorithm includes an energy management system (EMS) between renewables, batteries, and loads. Primarily, modeling of the system has been developed in MATLAB/Simulink environment. Additionally, case studies have been exemplified to further demonstrate the simulated system. Within this scope, certain load profiles not only have been fed but also power flow has been managed and analyzed to ensure effective and flexible operation with two different EMS cases. The real-time operation has been also provided to validate the system under various input and output conditions during a lab course.
Keywords: Microgrids; Batteries; Energy management; Load flow; Education; Load modeling; Wind turbines; Education laboratory; energy management system; distributed generation; microgrid; power electronic converters; renewable energy sources